Empathy (part II): contributions of nonviolent communication to clinical practice - Norman, Armando Henrique (2023)
Introduction: This article explores the issue of empathy in the doctor-patient relationship. Objective: To contribute to clinical communication skills through the empathy strategy proposed by nonviolent communication (NVC). Methods: Study of Marshall Rosenberg's main book, “Nonviolent Communication: A language of life”. Subsequently, several videos on YouTube were analyzed, both interviews and workshops with Rosenberg himself. A total of fifteen hours and eight minutes of audio-visual material was analyzed. Results: The selected content was organized into three sections: (1) NVC principles; (2) Empathy; and (3) Application of empathy in clinical practice. NVC contributes to the theme of empathy in clinical communication by proposing a model of empathic connection through the recognition of each person's feelings and needs. This model was organized into four stages: (a) observation without judgment; (b) connection with one's feelings; (c) unmet needs; and (d) the person's requests and demands. It is a synthesis, not only of communication, but also of intentionality and the conscious use of a language in the service of life, in what is alive in people at every moment. Conclusions: Empathy is a relevant topic in clinical communication. Because it is a complex subject, this study sought tools to facilitate its practical application. NVC can contribute to the strengthening of research and the exercise of empathy in clinical communication by filling possible gaps on the subject.